The use of indigenous Saccharomyces cerevisiae and Starmerella bacillaris strains as a tool to create chemical complexity in local wines. (September 2018) - Nisiotou, Aspasia; Sgouros, Georgios; Mallouchos, Athanasios; Nisiotis, Constantinos-Symeon; Michaelidis, Christos; Tassou, Chryssoula; Banilas, Georgios
Abstract: The performance of two vineyard strains, Saccharomyces cerevisiae SacPK7 and Starmerella bacillaris StbPK9, was evaluated in laboratory and pilot scale fermentations of Cretan grape must under the following inoculation schemes: single inoculation of SacPK7 (IS), simultaneous inoculation of StbPK9 and SacPK7 (SM), and sequential inoculation of StbPK9 followed by SacPK7 (SQ). Un-inoculated (spontaneous) fermentations (SP) and fermentations inoculated with control S. cerevisiae strains (CS) were also conducted as reference. Star. bacillaris not only did not restrict but also slightly promoted the growth of S. cerevisiae when the two strains were co-inoculated at equal quantities. On the contrary, the SQ inoculation scheme conferred a competitive advantage to Star. bacillaris over S. cerevisiae, which maximum population was reduced, while increased levels of Star. bacillaris were recorded. The fermentation kinetics were also affected, accordingly. The completion of fermentation was faster in SM, IS and CS ferments than in SQ and SP. Ethanol accumulation had a predominant role in the early death of Star. bacillaris, since its growth was similarly arrested irrespective of the dominating yeast species, the magnitude of yeast population or the availability of energy sources. Interestingly, the inoculation scheme applied significantly affected the chemical profiles of the resulting wines. SQ produced the most divergent chemical profile in sterile must, with glycerol, acetic acid, acetaldehyde, residual glucose, malic acid, ethyl acetate and higher alcohols being the key compounds affected by the prolonged activity of StbPK9. In pilot scale ferments, the indigenous S. cerevisiae produced twice as high levels of esters and higher alcohols compared to the commercial starter. Star. bacillaris further increased the levels of ethyl esters in the respective ferments. The use of a mixed S. cerevisiae/Star. bacillaris starter culture instead of S. cerevisiae alone enhanced the chemical complexity of Cretan local wine. The magnitude of differentiation was even higher when the addition of Star. bacillaris preceded that of S. cerevisiae . The highest divergence in analytical profiles was recorded between wines produced by native strain combinations and commercial S. cerevisiae . Present results show that the use of indigenous yeast formulations provides significant diversification to local wines, in line with the microbial terroir concept and recent observations that indigenous yeast strains may confer regional characters to wines. Graphical abstract: Unlabelled Image Highlights: Wine diversification is promoted when a mixture of NS/ S. cerevisiae is applied. The chemical profile of wines is significantly affected by the inoculation scheme. Sequential inoculation in sterile must produce the most divergent chemical profile. Indigenous yeasts may provide significant diversification to local wines.